A novel bioadhesive semisolid formulation containing chitosan and tetracycline/layered clay complexes for local delivery into periodontal pocket. (November 2014) - Aguzzi, C.; Sandri, G.; Cerezo, P.; Ferrari, F.; Rossi, S.; Bonferoni, C.; Caramella, C.; Viseras, C.
Abstract : An intrapocket non-conventional bioadhesive semisolid formulation based on tetracycline layered clay complexes and chitosan was developed to ensure extended drug release properties and adequate permanence time at the site of action. A Dohelert experimental design was used to discriminate among seven possible formulations, using viscosity as response variable. The formulation containing chitosan 2% (w/w) and complex (15% w/w) was selected as better candidate and was characterised for rheological behaviour, bioadhesive properties, microbicidal effect and drug delivery features. The formulation maintained the antibacterial activity of the drug against Streptococcus vestibularis, reaching a complete inactivation of bacterial cells after 24 h. The presence of the complex in the formulation not only did not induce any change in the intrinsic bioadhesive properties of chitosan, ensuring a good permanence time in the site of application but also resulted in drug release/wash away profiles compatible with a once a week administration of tetracycline HCl into the periodontal pocket.